COMPARISON OF DIAGNOSTIC PERFORMANCE AND CLINICAL UTILITY OF DIFFERENT HBA1C CRITERIA AGAINST ORAL GLUCOSE TOLERANCE TEST (OGTT) IN SCREEN DETECTION OF DIABETES IN PENANG, MALAYSIA - MN, Juliana; G, Kurubaran; P, Janisha; M, Tsu Horng; N, Serene; P, Yun Xin; M, Delis Suzan; C, Chen Joo; S, Purnima Devi; H, Chee Peng; et al. (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Glycated haemoglobin (HbA1c) cut-off of 6.5% has been recommended for diagnosing diabetes mellitus. However, HbA1c levels can vary due to functional glucose-independent attributes like ethnicity, which could influence diagnostic performance across different populations. The Malaysian Clinical Practice guideline advocates a lower HbA1c diagnostic cut-off of 6.3% based on one large national study. This study compared the diagnostic performance and clinical utility of HbA1c cut-offs of 6.5% and 6.3%, against the gold standard OGTT in diagnosing diabetes. METHODOLOGY A total of 298 subjects without diabetes aged ≥30 years old were purposively sampled across general hospitals, health clinics and community centers in Penang between February 2016 and December 2017. HbA1c cut-offs of 6.3% and 6.5% were validated against the 2-hour OGTT results. Sensitivity, specificity and predictive values were analyzed using SPSS version 22.0. Likelihood ratios (LR) with 95% CIs for diagnostic accuracy were yielded using MedCalc statistical software. RESULTS The sample constituted of 175 (58.7%) women and 123 (41.3%) men with mean age (50.9±11.5 years) and mean BMI (26.4±5.50 kg/m2). The prevalence of diabetes was 21.8% using OGTT, 22.8% using an HbA1c cut-off of 6.5% and 30.2% using an HbA1c cut-off of 6.3%. At HbA1c level of 6.5%, the sensitivity was 72.3% and specificity was 91% with positive and negative predictive values of 69% and 92%. Likelihood ratios (LR+ and LR-, 95% CI) were 8.0 (5.2- 12.39) and 0.3 (0.2-0.5), respectively. In contrast, HbA1c cut-off of 6.3% yielded a sensitivity of 84.6%, specificity of 85% with positive and negative predictive values of 61% and 95%. Likelihood ratios (LR+ and LR-, 95% CI) were 5.6 (4.1-7.8) and 0.2 (0.1-0.3), respectively. CONCLUSION HbA1c cut off of 6.5% demonstrated better diagnostic performance and clinical utility compared to 6.3%. Larger studies are needed to identify the optimal HbA1c diagnostic criteria for multiethnic Malaysia.